Open-source hardware as a model of technological innovation and academic entrepreneurship: The Brazilian landscape - Vinícius Rosa Cota; Cleiton Lopes Aguiar; BezamatBenegas de Souza Neto (Innovation & Management Review, 2020)
Purpose - The purpose of this paper is to argue in favor of the open hardware philosophy (open-source hardware - OSH) as a technological innovation and academic entrepreneurshipmodel in Brazil. Design/methodology/approach This argument is based on three pillars. The first one refers to a bibliographic review of theoretical frameworks related to academic entrepreneurship and technological innovation to emphasize the disruptive innovation capacity of academia. Second, a few elements related to the Brazilian political, economic and structural scenario, which entail a (more) favorable environment to technological innovation and academic entrepreneurship, is presented. Finally, concepts related to OSH and its business model are approached to demonstrate the facilitating effect toward the whole process. Findings As a result of the argument made herein, it is possible to perceive the viability of the OSH model in terms of entrepreneurship and technological innovation in the academic sphere, and to perceive its benefits before social and economic needs in areas such as health and education. Research limitations/implications There are no empirical or quantifiable data in the literature that enable comparison between OSH and traditional technological innovation models. Originality/value The considerations on the philosophical value of OSH and its business models are scarcely explored in international literature. As far as we know, relating OSH to technological innovation entrepreneurship in the academic sphere, as well as its singularities in Brazil regarding the innovation national system and social and economic demands, is a unique approach in literature.
Keywords: 650; Academia; Ciência; Empreendedorismo; Inovaç\~ao; Open-source hardware; Tecnologia